Introducing an innovative immobilized optode based on PVC-ETH-5294 matrix for environmentally friendly sensing of lead ions - Reem F. Alshehri; Alaa S. Amin; Eman R. Darwish (Talanta Open, 2024)
A novel selective membrane optode was prepared to determine of ultra-trace amounts of lead. This state-of-the-art optode amalgamates a bespoke ionophore, 4-(thiazol-2-yldiazenyl)benzene-1,3-diol (TDBD), with ETH-5294, assuming the role of a chromoionophore. This potent composition converges with sodium tetraphenylborate (NaTPB) and dioctyl phthalate (DOP), harmoniously enclosed within a matrix of poly(vinyl chloride) (PVC). The influence of various parameters on the preparation of the optode and the determination of Pb2+ was investigated and optimized. Evidently, the optode unfurls an expansive linear dynamic expanse, spanning an astonishing range from 6.0 × 10−9 to 8 × 10−5 M. Remarkably, it retains an astonishingly low degree of detection and quantification, registering at 1.75 and 5.85 × 10−9 M, respectively. The response time of the optode was 4.0 min. The optodes versatility extends its embrace towards rejuvenation, permitting multiple rounds of service via 0.2 M HNO3 solutions. The effect of potential interference ions on the Pb2+ determination was illustrated. The results showed that the prepared optode was very selective to lead ions so that it had no significant response to common ions such as Mg2+, Mn2+, Cd2+, Ni2+, Fe2+, Fe3+, Hg2+, Cu2+, and Co2+. The optode was applied successfully to determine of Pb2+ indifferent food, biological and environmental samples and result obtained is comparable to atomic absorption spectrometry method.